2016
DOI: 10.1002/ajim.22550
|View full text |Cite
|
Sign up to set email alerts
|

Expecting the unexpected: A mixed methods study of violence to EMS responders in an urban fire department

Abstract: BackgroundStruck by injuries experienced by females were observed to be higher compared to males in an urban fire department. The disparity was investigated while gaining a grounded understanding of EMS responder experiences from patient‐initiated violence.MethodsA convergent parallel mixed methods design was employed. Using a linked injury dataset, patient‐initiated violence estimates were calculated comparing genders. Semi‐structured interviews and a focus group were conducted with injured EMS responders.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 6 publications
2
58
0
Order By: Relevance
“…However, about 6% of the cases of violence against EMS personnel were perpetrated by friends or family members of the patient . In other studies, about 4% of physical assaults were perpetrated by a “colleague” and bystanders were perpetrators for some cases …”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…However, about 6% of the cases of violence against EMS personnel were perpetrated by friends or family members of the patient . In other studies, about 4% of physical assaults were perpetrated by a “colleague” and bystanders were perpetrators for some cases …”
Section: Resultsmentioning
confidence: 95%
“…This review demonstrated that there is a paucity of published data on critical questions such as how risks of violence for EMS personnel may vary based upon demographic factors. Three studies published between 2006 and 2016 found that female EMS personnel had higher risks of violence than males . Maguire found that female EMS personnel have a higher overall rate of injuries than male EMS personnel and that female EMS personnel might have a higher risk of homicide than males .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emergency medical service (EMS) providers are subject to workplace violence, including sexual harassment and abuse . Sexual harassment is defined as “unwanted sex‐related behavior at work that is perceived by the recipient as offensive, exceeding the individual's coping resources or threatens their well‐being.” In a study of 260 paramedics, 38% of women and 10% of men experienced sexual harassment in the preceding 12 months .…”
Section: Introductionmentioning
confidence: 99%
“…In first responder industries men have described not reporting violence for fear of not looking ‘macho’,9 while women have discussed adherence to reporting as a way to protect their tenure and employee health benefits 10. This has been hypothesised to drive increased reporting of violence by women versus men in first responder industries.…”
mentioning
confidence: 99%